RFID Application Framework for Theme Park Management System: Sunway Lagoon Theme Park - Chong, Kon Ming (2008)
The technology for Radio Frequency Identification (RFID) enables data to be transmitted by a tiny portable device, called a tag, which is read by an RFID reader and processed according to the needs of a particular application. It is only recently that the technology has begun to take off in the mass market. Analysts predict that RFID will revolutionize areas of industry, such as Supply Chain Management (SCM), Customer Relationship Management (CRM), and the retail business, for example by reducing costs with better stock management. This paper focuses on the application of RFID technology framework in Theme Park Management System.